Zarządzanie środkami finansowymi z funduszy strukturalnych Unii Europejskiej - Tosik, Amelia (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The prevailing general economic crisis, which coincided with the constitutional crisis in the European Union, exposed the challenges facing the Union. Future years will determine whether the EU institutional reform introduced in the Treaty of Lisbon will affect the effi ciency and speed of recovery from the crisis. One of the elements reducing anti-economic growth and maintaining positive trends in social development is the EU structural funds. Investments co-fi nanced from EU funds help to create the material basis for economic development in the future, when the process of economic recovery starts and an upward trend returns. In this context, the implementation of the general budget of the EU takes signifi cant importance, although there were and may still appear new problems which should have been predicted. The purpose of the article is to provide legal solutions in the fi eld of fi nancial management of EU structural funds as well as institutional arrangements associated directly or indirectly with the shared management of these funds, which are based on existing treaty regulations. The author shall consider whether the management of EU funds under the so-called shared management and the control mechanisms are the optimal solution to ensure proper management of the EU budget and protection of its fi nancial interests
Keywords: prawo; ekonomika prawa; instytucje prawne; fundusze strukturalne; polityka spójności; budżet; zarządzanie; Unia Europejska